Software solutions for engineers and scientists - Sanchez, Julio, 1938- (CRC Press, 2008)
Development tools and practical shortcuts are provided for professionals who already have basic programming skills but may lack the knowledge needed to perform sophisticated tasks. The book includes mathematical-computation intensive code along with programming techniques compatible with Visual C++ and Windows program applications.